Pazopanib and depot octreotide in advanced, well-differentiated neuroendocrine tumours: a multicentre, single-group, phase 2 study. Issue 6 (June 2015) - Phan, Alexandria T; Halperin, Daniel M; Chan, Jennifer A; Fogelman, David R; Hess, Kenneth R; Malinowski, Paige; Regan, Eileen; Ng, Chaan S; Yao, James C; Kulke, Matthew H
Summary: Background: Treatment options for advanced, well-differentiated neuroendocrine tumours (NETs) remain scarce. Pazopanib is an orally bioavailable, small molecule, multitargeted kinase inhibitor that inhibits VEGF receptors 1, 2, and 3. We did a study of the efficacy of pazopanib with depot octreotide in patients with advanced NETs. Methods: We did a parallel cohort study of patients with metastatic or locally advanced grade 1–2 carcinoid tumours or pancreatic NETs, by use of a single-group, two-stage design. Patients received pazopanib 800 mg orally once per day and octreotide at their preprotocol dosage. The primary endpoint was the proportion of patients achieving an objective response, as assessed by investigators, by intention-to-treat analysis. This study is registered withClinicalTrials.gov, identifierNCT00454363, and was completed in March, 2014. Findings: Between April 12, 2007, and July 2, 2009, we enrolled 52 patients, including 32 individuals with pancreatic NETs and 20 individuals with carcinoid tumours. Seven (21·9%, 95% CI 11·0–38·8) of 32 patients with pancreatic NETs achieved an objective response. We detected no responses in the first stage of the cohort with carcinoid tumours, and we terminated accrual at 20 patients. Toxic effects included one patient with grade 4 hypertriglyceridaemia and one with grade 4 thrombosis, with the most common grade three events being aminotransferase increases and neutropenia, each of which happened in 3 patients. In all 52 patients, the most frequently observed toxic effects were fatigue (39 [75%]), nausea (33 [63%]), diarrhoea (33 [63%]), and hypertension (28 [54%]). Interpretation: Treatment with pazopanib is associated with tumour response for patients with pancreatic NETs, but not for carcinoid tumours; a randomised controlled phase 3 study to assess pazopanib in advanced pancreatic NETs is warranted. Funding: US National Cancer Institute of the National Institutes of Health.